2018
DOI: 10.1590/1806-90882018000500001
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF PLANT SPACING ON THE BARK PROPERTIES OF A Eucalyptus CLONE

Abstract: For several wood uses, such as pulp, paper and charcoal, the presence of the bark is undesirable, compromising production. Thus, this study aimed to evaluate the influence of different plant spacings on the properties of the bark of a clone of Eucalyptus grandis x E. camaldulensis at seven years of age at five different plant spacings. The wood discs were removed from the trees at 0, 25, 50, 75 and 100% of the commercial height; then we performed thickness, basic density, gross calorific value and mineral cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…In Brazil, Rocha et al (2016) assessed the influence of plant spacing on wood and bark density in 7-year-old Eucalyptus hybrids grown in northern Minas Gerais, Brazil and concluded that trees at wider spacings (9 m 2 ) produce bark with greater density than at narrowed spacings (1.5 m 2 ). Rocha et al (2018) evaluated the effect of different plant spacings on bark thickness and properties in Eucalyptus grandis × E. camaldulensis and reported that plant spacing positively affects bark properties. Martins et al (2019) have quantified the macronutrients of 12-year-old Eucalyptus bark planted at three planting densities, concluding that higher plant density contributed to higher bark production and greater nutrient accumulation per area.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, Rocha et al (2016) assessed the influence of plant spacing on wood and bark density in 7-year-old Eucalyptus hybrids grown in northern Minas Gerais, Brazil and concluded that trees at wider spacings (9 m 2 ) produce bark with greater density than at narrowed spacings (1.5 m 2 ). Rocha et al (2018) evaluated the effect of different plant spacings on bark thickness and properties in Eucalyptus grandis × E. camaldulensis and reported that plant spacing positively affects bark properties. Martins et al (2019) have quantified the macronutrients of 12-year-old Eucalyptus bark planted at three planting densities, concluding that higher plant density contributed to higher bark production and greater nutrient accumulation per area.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of approximately 8% in the mean basic density was verified for spacings from 1.5 to 4.5 m 2 and 9.0 m 2 for Eucalyptus plantations (Rocha et al 2016). The largest spacings might result in earlier formation of mature wood, as observed for wood from Eucalyptus (Malan and Hoon 1992).…”
Section: Physical and Anatomical Properties Of T Vulgaris Woodmentioning
confidence: 56%
“…Besides differences in genetic quality, climate and site quality have strong effects on forest productivity and wood quality, decisively affecting its end use (Larson et al 2001). Another factor to consider is that with higher productivities, the harvesting ages are declining, to the point where there is insufficient time to obtain mature wood from clonal stands, so that the wood harvested is all juvenile (Santos et al 2016, Rocha et al 2018). Add to this the fact, wood characterization results usually cannot be extrapolated from one place or climate to other because a single clone as a function of its genetic plasticity can express its anatomical traits in different ways from one place to another.…”
Section: Introductionmentioning
confidence: 99%